A case series of percutaneous tension band wiring technique for fixation of fractures of olecranon and patella - Khandelwal, R. C. S.; Shah, Swapneel; Sanghvi, Umang; Agrawal, Aditya K. (International Journal of Research in Orthopaedics, 2022)
There are several advantages in the treatment of fractures by means of closed reduction. Percutaneous fixation is a type of biological fixation. The aim and objectives of this study are to demonstrate the technique of percutaneous tension band wiring in cases of transverse, non- comminuted olecranon and patella fractures and to decrease the soft tissue dissection, blood loss, chances of infection and to ensure speedy mobilization using the innovative percutaneous fixation technique. This retrospective study includes ten patients of olecranon and ten patients of patella operated by the same surgeon. All patients were operated with percutaneous tension band wiring for olecranon and patella. There were six males and four females with olecranon fractures. There were seven males and three females who suffered patella fractures. The average duration of surgery was 55 minutes and average follow up was 24±6 weeks. The suture removal was done at 2 weeks. All patients had full range of movements at six weeks with significantly improved DASH score and Oxford knee score. None of the patients had any complications. Percutaneous fixation decreases the chances of bleeding secondary to unnecessary soft tissue dissection, thereby decreasing the post-operative morbidity. It also, convincingly, decreases the chances of post-operative infection and promotes early mobilization. Closed reduction with percutaneous fixation is believed to be an innovative, safe, reliable and efficient method of managing these difficult fractures.